Kewenangan Pemerintah Aceh dalam Bidang Pengelolaan Hutan di Provinsi Aceh - Arnita Arnita (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: The authority of local government is regulated in act No.32 Tahun 2004 about the regional government, just for Aceh in Act No. 11 Tahun 2006 about Aceh Government. From the two act local government has the authority in forest managament, but in Leuseur Forest managament The authority of the Government Aceh must be bent down for the national general act about the forest. Because the Leuser Forest is one of the World Heritage, in managing forest to prevent it from causing a damage or pollution direct or indirectly to the environment. The Authority of Aceh Government in Forest Management in Aceh Province